New York Paper - Tests on Various Electric Motor-Driven Equipment Used in the Preparation of Anthracite Coal (with Discussion) - H. M. Warren; A. S. Biesecker; E. J. Powell (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1916)
In the past, steam engines were used in practically all cases for driving the machinery in and about an anthracite breaker, and hence few or no accurate data were available as to the power requirements for starting and operating the individual machines, which make up the complete equipment. It was impossible to segregate the power necessary to drive each individual machine, first, because the equipment was driven in groups, and second, because it was impracticable to obtain graphic, integrated, or instantaneous records of the horsepower used. As a result of these conditions, it was found, when individual electric motors were applied to the various machines, that more accurate and complete data were needed in order to provide motors of the proper power and design for the particular services to be rendered. In order to obtain the desired information, the writers made and collected a number of tests, from time to time, on the individual motor drives in electrically operated breakers, and as these tests have been of great value, it occurred to them that a paper giving the results might be of service to other engineers interested in similar installations. Table I shows the results of these tests. All the motors tested were of the three-phase, 60-cycle, 440-volt, induction, squirrel-cage type, except a few, which, on account of size and starting conditions, were of the wound-rotor type. The instruments used in making these tests were: An integrating watt-hour meter, a graphic ammeter, and a graphic voltmeter. These instruments were connected in each motor circuit, and a record of a day's run of 9 hours was obtained from each machine. From these tests, the running light load, the average all-day load, and the instantaneous peak readings in amperes, volts, and kilowatt input, were obtained. By means of the characteristic curves obtained from these motors at the factory, the power factor, the efficiency, and the horsepower output were calculated for each particular test. Starting tests were made by the brake-arm method, in which the torque in pounds was measured directly on a spring balance.